(untitled) (Swiss Medical Weekly, 2014)
The term myocarditis describes inflammatory disorders of the heart muscle of varied infectious and non-infectious origins. It can be caused by any kind of infection, drugs, toxic substances, or be associated with autoimmune conditions. Viruses are the main causes at least in developed countries. Acute myocarditis most commonly results from an external inflammatory trigger inducing the host immune response, which may range from minimally transient response to fulminant overwhelming cellular infiltration. If the immune system does not eliminate the infectious pathogen early on, chronic infection develops with or without accompanying inflammation. Post-infectious autoimmunity may persist despite effective virus clearance. Since the pathological conditions take place at the cellular level, viral myocarditis and postinfectious autoimmunity can be suggested but not diagnosed clinically. All clinical methods including imaging techniques are misleading if infectious agents are involved. Accurate diagnosis demands simultaneous histologic, immunohistochemical and molecular biological workup of the tissue. If the primary infectious or immune-mediated causes of the disease are carefully defined by clinical and biopsy based tools, specific antiviral treatment options in addition to basic symptomatic therapy are available under certain conditions. These may allow a tailored cause-specific treatment that improves symptoms and prognosis of patients with acute and chronic disease.